2020
DOI: 10.3390/ani10091702
|View full text |Cite
|
Sign up to set email alerts
|

Abilities of Canine Shelter Behavioral Evaluations and Owner Surrender Profiles to Predict Resource Guarding in Adoptive Homes

Abstract: Some shelters in the United States consider dogs identified as food aggressive during behavioral evaluations to be unadoptable. We surveyed adopters of dogs from a New York shelter to examine predictive abilities of shelter behavioral evaluations and owner surrender profiles. Twenty of 139 dogs (14.4%) were assessed as resource guarding in the shelter. We found statistically significant associations between shelter assessment as resource guarding and guarding reported in the adoptive home for three situations:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…It is worth noting, however, that even though scores on food guarding tests predicted length of stay (present study) and likelihood of return [ 16 ] at our study shelter, food guarding during shelter testing did not consistently signal such guarding would occur in adoptive homes. Surveys of adopters revealed that more than half of the dogs evaluated as food guarding at our study shelter did not show guarding postadoption [ 7 ]; similar findings have been reported for dogs at other shelters [ 5 , 6 ].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…It is worth noting, however, that even though scores on food guarding tests predicted length of stay (present study) and likelihood of return [ 16 ] at our study shelter, food guarding during shelter testing did not consistently signal such guarding would occur in adoptive homes. Surveys of adopters revealed that more than half of the dogs evaluated as food guarding at our study shelter did not show guarding postadoption [ 7 ]; similar findings have been reported for dogs at other shelters [ 5 , 6 ].…”
Section: Discussionsupporting
confidence: 79%
“…To be consistent with previously published research, we categorized data from the Food bowl test and Possession test somewhat differently than the above descriptions for other tests. First, studies of resource guarding in shelter dogs typically combine results from these two tests [ 6 , 7 , 16 ], so we combined them in our analyses as well. Second, previous studies classified the level of guarding based on behaviors shown during either the food bowl test, possession test, or both tests as follows: dogs that stiffened, exhibited whale eye, snarled, froze, or growled were classified as showing mild to moderate guarding, and dogs that lunged, snapped, or bit the Assess-a-Hand were classified as showing severe guarding [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has several limitations. First, canine behavioral evaluations at shelters have been criticized for their lack of rigorous scientific validation and poor predictability of many post-adoption behaviors [8,[31][32][33]. However, proponents view these evaluations as one of several sources of information about dogs in shelters [24,34].…”
Section: Discussionmentioning
confidence: 99%